Recovery of Solar Energy for Powering Small Device as Wireless Communicating Nodes - Diagne, Salick; Farota, Abdou Karim; Assogba, Ognadon; Diop, Bouya; Val, Thierry (Technological Innovation in Engineering Research Vol. 1, 2022)
We constructed and simulated a solar energy recovery and storage system for wireless sensors in this research. To do so, we modelled each component: the solar panel, the adaption circuit (in which we employed the disturb and observe command in conjunction with fuzzy logic to find the MPP), and the supercapacitor for energy storage. This study is part of a project to protect Senegal's rice fields against grain-eating birds using wireless sensors and actuators. In this wireless communication technology between objects, energy consumption is a crucial point. Indeed, it defines the lifespan of applications based on this technology. A solar energy recovery and storage system for powering wireless sensors was devised and modelled in this work. To do so, we modelled each component, including the solar panel, the adaption circuit, which employed the disturb and observe command in conjunction with fuzzy logic to find the MPP, and the supercapacitor for energy storage. The study also employed supercapacitor technology to store energy. The models' simulations yield appropriate findings for a wireless communication node's autonomous power supply in the study region.